Nanotechnology in biology and medicine : research advancements & future perspectives - Rauta, Pradipta Ranjan; Mohanta, Yugal Kishore; Nayak, Debasis (New York, NY : CRC Press, 2019)
"The book is focused to provide an overview on the developments made in nanotechnology till date along with the ongoing trends and the future prospects. It also present the basics, fundamental results and latest achievements in nanobiotechnological researches"--
3.11 Applications of Algae in Nanotechnology3.11.1 Application of Nanospheres in the Transesterification Reaction; 3.11.2 Application of Diatoms in Waste Degradation and Metal Toxicity; 3.11.3 Application of Nano-Cellulose from Algae in Electrical Insulators; 3.11.4 Applications of Diatoms in the Electronics Industry; 3.11.5 Applications of Coccoliths in Nanotechnology; 3.12 Conclusion; References; Chapter 4: Liposome Nanocarrier Synthesis, Characterization, and Applications; 4.1 Introduction; 4.2 Structure of Liposomes; 4.2.1 Phospholipids; 4.2.2 Cholesterol; 4.3 Classification of Liposomes
OCLC-licensed vendor bibliographic record.
Keywords: Nanobiotechnology; Nanotechnology; Medical technology; MEDICAL / Biochemistry; MEDICAL / Biotechnology; SCIENCE / Life Sciences / General